Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Plazooooooooo oooooooooooooooooooo solve question number 26.

Plazooooooooo oooooooooooooooooooo solve question number 26.

Question Image
Grade:11

2 Answers

Manda Snehashish Reddy
113 Points
3 years ago
FInd your answer below and if found helpful please vote for it
a – 3b = -6
a3-27b3-9ab(a-3b) = -216
a3-27b3-9(-10)(-6) = -216
a3-27b3 = -216 + 540
a3-27b3 = 324
Ram Kushwah
110 Points
2 years ago
a3-27b3=(a-3b) [(a-3b)2+3*a*3b]a – 3b = -6So 
=-6*(36 +9ab)
=-6*[ 36+9*(-10)]
=-6*(36-90)
=-6*(-54)
=324

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free